Field notes contributed by Dean Mosman, winter 1982-1983 - Mosman, Deanet al (1982)
Winter report of birds seen as well as the many species that were not seen during the winter season of 1982-1983 contributed by Dean Mosman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed